APLIKASI PENCARIAN LOKASI FASILITAS PELAYANAN UMUM TERDEKAT MENGGUNAKAN METODE ARTIFICIAL BEE COLONY DI KOTA BENGKULU BERBASIS WEBVIEW ANDROID - Eno Rahmandha; Rusdi Efendi; Diyah Puspitaningrum (Program Pascasarjana Magister Teknik Informatika, Universitas Dian Nuswantoro, 2017)
Public services are growing as concomitants of the Bengkulu’s population growth. That fact makes it hard to find a certain public service in Bengkulu city. Another reason is we need to find a nearby public service to do daily tasks. The purpose of tis research are: (1) to show a nearby public service’s location.(2) To implement Artificial Bee Colony method in Bengkulu City’s Public Services Finder using Webview Android. The results are: (1) This research managed to implement public services finder in to map;(2) The result of algorithm relevancy test using abc base is quite high, 81% relevant, Meanwhile for standard abcis 2.91%. (3) The best parameter setting is using bees (CS) 30,50. Maximum limit (L) 300,500,600 and maximum iteration (MCN) 30,50.(4) The best bees setting are (CS) 30, maximum limit (L) 1000 maximum iteration 50. Artificial Bee Colony linier relevancy using employed bees and defined iterations meanwhile maximum limit parameter is not taking effect on the algorithm.